COMPARISON OF COLOR IN AUTHENTICATION OF IDENTITY DOCUMENTS TASKS - E. I. Stepankova; N. A. Volorova (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
Method of color objects description in complex scenes and the algorithm of comparison of color tone on such objects using histogram method and quantization is presented. HSL color model is used in proposed algorithm. The size of objects and color can be arbitrary. Methods of objects detection can differ from discussed.